Strategi Penetapan Harga di Era Digital: Studi Kasus Perajin Bambu Lembur Awi - Lika Mawardani; Yanto Yanto (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The development of the digital era brings new challenges and opportunities for micro businesses, especially in pricing bamboo handicraft products in Lembur Awi. The phenomenon of easy access to information and digital marketing makes it easier for consumers to compare prices, so pricing strategies become a crucial factor in maintaining business competitiveness. This study aims to analyze the pricing strategy applied by bamboo handicraft micro businesses in Lembur Awi, identify factors that influence pricing, and understand the influence of digital platforms on the pricing strategy. The research method used was a qualitative approach with a case study, involving in-depth interviews, observation and documentation as data collection techniques. The results showed that businesses use a pricing strategy based on the calculation of production costs adjusted to market conditions and digital competition. The utilization of digital platforms such as social media and e-commerce provides opportunities to expand the market while demanding adaptation of pricing strategies that are more flexible and responsive. Good financial management and integrated administrative systems also play an important role in making effective pricing decisions. This research concludes that a combination of costing, utilization of digital technology and product innovation is key to the success of bamboo craft businesses in the dig era.